GC-MS ANALYSIS OF THE AQUEOUS EXTRACTS OF BUCHHOLZIA CORIACEA ENGL (CAPPARIDACEAE), SEEDS.: Pharmaceutical Science-Phytochemistry - OMOREGIE GLORIA OMOROWA; MACDONALD IDU; OVUAKPORIE-UVO OGHALE. (International Journal of Life Science and Pharma Research, 2022)
Buchholzia coriacea E. is one of the medicinal plants of importance belonging to the family Capparidaceae. Investigations aimed at identifying and isolating the major chemical compounds in Buchholzia coriacea aqueous seed extracts using Gas chromatography-Mass spectrometry (GC-MS) method was carried out. Results showed that Buchholzia coriacea aqueous seed extract contains six (6) bioactive compounds namely; Phenol, 3,5-bis(1,1-dimethylethyl); Hexadecanoic acid, 15-methyl-, methyl ester; n-Hexadecanoic acid; Cyclopropaneoctanoic, 2-hexyl-, methyl-, methyl ester;(Z)-Docos-13-enoic acid and 9,12-Octadecadienoyl chloride (Z,Z)-. (Z)-Docos-13- enoic acid was the prevailing compound with Retention Time (RT) of 22.850 and a peak area of 76.63. Finding suggests that (Z)-Docos-13-enoic acid could be an anti-oxidant.